Transformational Leadership in Organizational Change of Nepalese Banking Organization - Rijal, Madhu (Journal of Kathmandu BernHardt College, 2023)
This seminar report explores into the impact of transformational leadership on organizational change in Nepal’s organizational sector, emphasizing its ability to inspire innovation and adaptability among employees. It highlights the challenges faced by Nepalese industries and the need for strategic organizational transformations. Through a conceptual lens, the report underscores the importance of transformational leadership, encompassing idealized influence, consideration, intellectual stimulation, innovation, and inspirational motivation. By fostering intellectual stimulation and inspiring employees, transformational leaders facilitate the generation of new knowledge and drive organizational change effectively. The study offers managerial insights and research recommendations tailored to the dynamic and globalized landscape of today’s business environment.